Between Paris and Lima, from the Search for Filial Inheritance to Authorship and Socialist Feminism in Memorias de Una Paria by Flora Tristán; [Entre París y Lima, de la Búsqueda de Herencia Filial a la Autoría y Al Feminismo Socialista en Memorias de Una Paria de Flora Tristán] - Jeftanovic-Avdaloff, A; Garrido-Ayala, L (Universidad Catolica Silva Henriquez, 2024)
This article proposes to look at the case of the French-Peruvian writer and feminist Flora Tristán, as a traveling person who moves from France to Peru, her paternal homeland, to constitute or complete a truncated, illegitimate identity. That enterprise fails according to what is narrated in her memoirs, forcing Tristán to redefine her "journey" and place in the world. We are interested in looking at this "trajectory" as a personal journey of a human being lacking a name and solid identity who goes in search of symbolic and material recognition, which she obtains by herself, from the creation of literary works and her participation in feminist social movements. This implies analyzing the functioning of the new supports of her identity: literature, feminism and political activism. © 2024 Universidad Catolica Silva Henriquez. All rights reserved.